2016
DOI: 10.4103/0259-1162.164677
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia after inguinal hernia repair - Comparison of ropivacaine with bupivacaine: A randomized controlled trial

Abstract: Background:Postoperative pain management by surgical site infiltration has an edge over other methods of analgesia as it is simple and has lesser side effects. This study was designed to compare the analgesic effects provided by bupivacaine, a classical long-acting local anesthetic and ropivacaine, a new amino amide local anesthetic agent.Subjects and Methods:Ninety patients scheduled for elective inguinal herniorrhaphy were randomly allocated to one of the three groups: Group I - R 0.5, group II - R 0.25, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In the current study, TAP block with 1 mg/kg of 0.25% ropivacaine successfully provided pain relief in 87% of the pediatric patients immediately after surgery, and reduced the need for fentanyl at PACU by 67%. Limited studies have investigated the effect of different concentrations and volumes of local anesthetics in regional anesthesia [11,12,13]. In children undergoing orchiopexy, caudal block, with a large volume of diluted ropivacaine, provided better quality and a longer duration of analgesia than a small volume of concentrated ropivacaine [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, TAP block with 1 mg/kg of 0.25% ropivacaine successfully provided pain relief in 87% of the pediatric patients immediately after surgery, and reduced the need for fentanyl at PACU by 67%. Limited studies have investigated the effect of different concentrations and volumes of local anesthetics in regional anesthesia [11,12,13]. In children undergoing orchiopexy, caudal block, with a large volume of diluted ropivacaine, provided better quality and a longer duration of analgesia than a small volume of concentrated ropivacaine [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although, a higher dose of local anesthetics for regional nerve block provides prolonged relief from post-operative pain and decreases the need for rescue analgesics [12,13], it is worthwhile to investigate the optimal concentration and volume for the same dosage of local anesthetics owing to a perennial risk of overdose, due to local anesthetics, especially in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early discharge from hospital and significant analgesic effect is observed in all conducted studies. 8,9 Studies have likewise demonstrated prolong analgesic effect with the use of inguinal local infiltration along with decline in the usage of systemic analgesia after surgery. 10 The satisfaction of patient was also substantial.…”
Section: Original Articlementioning
confidence: 99%